Crizotinib efficacy and safety in patients with advanced NSCLC harboring MET alterations: A real-life data of Turkish Oncology Group. Issue 50 (16th December 2022) - Gürbüz, Mustafa; Kiliçkap, Saadettin; Bilici, Ahmet; Karadurmuş, Nuri; Sezer, Ahmet; Şendur, Mehmet Ali Nahit; Paydaş, Semra; Artaç, Mehmet; Fulden Yumuk, Perran; Gürsoy, Pinar; Uysal, Mükremin; Şenol Coşkun, Hasan; et al.
Abstract : Crizotinib is a multikinase inhibitor, effective in non-small cell lung cancer (NSCLC) harboring mesenchymal-epidermal transition (MET) alterations. Although small prospective studies showed efficacy and safety of crizotinib in NSCLC with MET alterations, there is limited real-life data. Aim of this study is to investigate real-life efficacy and safety of crizotinib in patients with advanced NSCLC harboring MET alterations. This was a retrospective, multicenter (17 centers) study of Turkish Oncology Group. Patients' demographic, histological data, treatment, response rates, survival outcomes, and toxicity data were collected. Outcomes were presented for the study population and compared between MET alteration types. Total of 62 patients were included with a median age of 58.5 (range, 26–78). Major histological type was adenocarcinoma, and 3 patients (4.8%) had sarcomatoid component. The most common MET analyzing method was next generation sequencing (90.3%). MET amplification and mutation frequencies were 53.2% (n = 33) and 46.8% (n = 29), respectively. Overall response rate and disease control rate were 56.5% and 74.2% in whole study population, respectively. Median progression free survival (PFS) was 7.2 months (95% confidence interval [CI]: 3.8–10.5), and median overall survival (OS) was 18.7 months (95% CI: 13.7–23.7), regardless of treatment line. Median PFS was 6.1 months (95% CI: 5.6–6.4) for patients with MET amplification, whereas 14.3 months (95% CI: 6.7–21.7) for patients with MET mutation ( P = .217). Median PFS was significantly longer in patients who have never smoked ( P = .040), have good performance score ( P < .001), and responded to the treatment ( P < .001). OS was significantly longer in patients with MET mutation (25.6 months, 95% CI: 15.9–35.3) compared to the patients with MET amplification (11.0 months; 95% CI: 5.2–16.8) ( P = .049). In never-smokers, median OS was longer than smoker patients (25.6 months [95% CI: 11.8–39.3] vs 16.5 months [95% CI: 9.3–23.6]; P = .049). The most common adverse effects were fatigue (50%), peripheral edema (21%), nausea (29%) and diarrhea (19.4%). Grade 3 or 4 adverse effects were observed in 6.5% of the patients. This real-life data confirms efficacy and safety of crizotinib in the treatment of advanced NSCLC harboring MET alteration.